Use of quality tools in reducing rework: an exploratory study in the metal-mechanical industry - Lima, Gislayne de Souza de; Cordeiro, Nelly Heine Marques; Garcia, Mario Vinicio; Gomes, Henrique Costa (Brazilian Journal of Production Engineering, 2026)
Quality is currently a fundamental factor in organizations, as increasingly fierce competition and a highly competitive environment have made it essential for business survival. In production processes, quality is crucial to reducing problems, scrap, and losses. To achieve these objectives, several useful tools and methods are available. This study proposes the application of the PDCA Cycle, which aims to identify problems and generate actions to mitigate them. The purpose of the research was to apply PDCA to reduce rework in a company in the metal-mechanical sector, using quality tools to ensure the effective execution of all stages of the cycle, since this integration makes the process more reliable. This is an exploratory study whose methodology follows the logic of the cycle itself: planning, implementation of the proposed improvements, verification of the results, correction of failures, and standardization. After applying the method, it was possible to identify a reduction in rework in the company, in which the rate of rejected parts decreased from 1.63% to 0.8%, proving the effectiveness of the PDCA Cycle for addressing the case and highlighting its relevance as a continuous improvement tool in industrial processes.
Keywords: Quality; PDCA cycle; quality tools; rework reduction